Integrating Activity-Based Costing Into Environmental Management Accounting Information Systems: A Conceptual Framework and Research Agenda - Adrian Hartanto Darma Sanputra; Tatas Ridho Nugroho; Eka Ananta Sidharta; Ghina Mufidatus Salma; Ervina Dwi Aprilia; Nasya Nur Afifa (International Journal of Economics, Commerce, and Management, 2026)
Environmental Management Accounting Information Systems (EMAIS) have become essential infrastructure for organisations to identify, measure, and manage environmental costs in supporting sustainability objectives. However, their decision-usefulness remains limited because environmental costs are often hidden within general overhead, making the activities generating these costs unclear. Activity-Based Costing (ABC) offers a solution through activity-based cost tracing, yet its integration into EMAIS remains conceptually limited and empirically fragmented. Using previous bibliometric mapping and a theory-synthesis approach, this study develops the Activity-Based EMAIS (AB-EMAIS) framework. The framework incorporates ABC logic into the input, processing, and output layers of EMAIS architecture and expands it through artificial intelligence (AI) augmentation and governance and assurance layers. The framework produces nine testable propositions and a research agenda covering conceptual refinement, empirical validation, technological development, and contextual investigation. AB-EMAIS transforms ABC–EMAIS integration into a coherent design framework, supporting transparent, relevant, and accountable environmental cost information. The framework is particularly relevant for emerging economies advancing Sustainable Development Goal 12.